The Effect on Carburizing Process on Microstructure and Properties of 20MnCr5 Gear Steel. Issue 2 (April 2021) - Liang, X.; Li, X.J.; Lin, X.Y.; Fan, Z.Y.; Luo, P.; Sun, F.L.; Gao, B.K.; Zhou, T.; Du, Q.N.; Xie, H.S.
Abstract: In this report, 20MnCr5 gear is characterized and analyzed under two carburizing heat treatment processes by optical microscope (OM) analysis, scanning electron microscope (SEM) analysis, X-ray diffraction (XRD) and Vickers hardness test. Results show that spherical and angular carbides can be obtained by a high concentration carburizing process for 20MnCr5 gear. Reheating and subsequent low-temperature tempering help refine the grains of the infiltration layer, reduce the residual austenite content in the permeable layer, and increase the thickness of the effective hardening layer.